Patients' sun practices, perceptions of skin cancer and their risk of skin cancer in rural Australia. (10th May 2019) - Sideris, Emily; Thomas, Susan J.
Abstract: Issue addressed: Skin cancer affects nearly one in three Australians. As a preventable disease there have been many public awareness campaigns targeting skin cancer knowledge and sun protection in Australia in the last 30 years to increase knowledge of the disease and how to prevent it. Despite higher incidence and mortality of skin cancer in regional Australia and adults over 65 years though, little research exists examining this high‐risk population's skin cancer knowledge and sun behaviours, with most previous research conducted in urban Australia or overseas. This study aimed to examine adults' skin cancer knowledge, sun behaviours and demographic factors in a regional Australian town. Methods: Cross‐sectional study design was utilised. Adult patients of a Mudgee General Practice (n = 179, 18‐89 years) completed a survey based on their skin cancer knowledge and sun behaviours. Chi‐squared tests were used to analyse responses. Results: Poor non‐melanoma skin cancer awareness, risky sun behaviours and inadequate sun protection behaviours were found. Males and those at greatest current risk of skin cancer in Australia, those over 60 years, had the poorest skin cancer knowledge and were least likely to recognise skin cancer or use some sun protection measures. Conclusions: Greater non‐melanoma skin cancer and sun protection education and research is needed, particularly targeting older and male Australians. So what?: The findings suggest rural men and older Australians would benefit from more targeted campaigns and education to increase their skin cancer awareness and use of sun protection in order to minimise future skin cancer.